A double‐leaf‐shaped four‐port MIMO antenna for ultra‐wideband applications. Issue 11 (3rd August 2022) - Garg, Rahul Kumar; Singhal, Sarthak; Nair, Maroor Vikraman Deepak; Tomar, Raghuvir
Abstract: A CPW‐fed double‐leaf‐shaped ultra‐wideband planar antenna, along with its four‐port MIMO configuration, is presented. The MIMO element is designed through combining the techniques of a modified radiator, coplanar waveguide feeding arrangement, and defected ground structure. The size and operating bandwidth of the MIMO element are 14 × 19 mm 2 and 3.73 GHz to 22.01 GHz, respectively. The MIMO element has a peak realized gain of 4.27 dBi and has stable radiation patterns at lower frequencies. In the MIMO configuration, four replicas of this MIMO element are orthogonally arranged to ensure polarization diversity. A rotated plus‐shaped decoupling structure is integrated with the MIMO design for enhancing intra‐element isolation. The proposed MIMO design offers an ultra‐wide bandwidth of 18.28 GHz (3.73 GHz–22.01 GHz), an isolation value of more than 22 dB and an overall footprint of 40 × 40 mm 2 . ECC < 0.03, CCL < 0.35, MEG < −4 dB, and TARC < −20 dB have been achieved. The MIMO design is fabricated and experimentally tested. The measured data is found to agree well with the simulated data. This antenna will be highly suitable for many ultra‐wideband communication applications in today's world.